Impact of Work Hour on Employee Social Wellbeing in Northern Ireland - Alshahrani, Mohammed Awad (European Scientific Journal, ESJ, 2019)
This paper aims to explore the relationship that exists between the amount of hour’s employees in Northern Ireland, work per week, and their social wellbeing represented by the level of happiness and Health status. This study made use ofsecondary data adapted from the 2009 Northern Ireland Life and Times Survey (NILT). Also, the study provides an analytic account of factors that determine the number of hours spent at work. The paper indicates that in Northern Ireland, there is no significant correlation between the amount of hours employee spent at work and their social wellbeing. Also, the study found that other factors such as: care for someone at home, sex, employed or self-employed, employment status, thinking about work, and socio-economic group significantly predicts the amount of time an employee in Northern Ireland spends at work. The study concluded that the relationship between work hour and employee social wellbeing varies across countries and cultures.